Steroidogenic electron-transfer factors and their diseases - Walter L. Miller (Korean Society of Pediatric Endocrinology, 2021)
Most steroidogenesis disorders are caused by mutations in genes encoding the steroidogenic enzymes, but work in the past 20 years has identified related disorders caused by mutations in the genes encoding the cofactors that transport electrons from NADPH to P450 enzymes. Most P450s are microsomal and require electron donation by P450 oxidoreductase (POR); by contrast, mitochondrial P450s require electron donation via ferredoxin reductase (FdxR) and ferredoxin (Fdx). POR deficiency is the most common and best-described of these new forms of congenital adrenal hyperplasia. Severe POR deficiency is characterized by the Antley-Bixler skeletal malformation syndrome and genital ambiguity in both sexes, and hence is easily recognized, but mild forms may present only with infertility and subtle disorders of steroidogenesis. The common POR polymorphism A503V reduces catalysis by P450c17 (17-hydroxylase/17,20-lyase) and the principal drugmetabolizing P450 enzymes. The 17,20-lyase activity of P450c17 requires the allosteric action of cytochrome b5, which promotes interaction of P450c17 with POR, with consequent electron transfer. Rare b5 mutations are one of several causes of 17,20-lyase deficiency. In addition to their roles with steroidogenic mitochondrial P450s, Fdx and FdxR participate in the synthesis of iron-sulfur clusters used by many enzymes. Disruptions in the assembly of Fe-S clusters is associated with Friedreich ataxia and Parkinson disease. Recent work has identified mutations in FdxR in patients with neuropathic hearing loss and visual impairment, somewhat resembling the global neurologic disorders seen with mitochondrial diseases. Impaired steroidogenesis is to be expected in such individuals, but this has not yet been studied.